Pre-service teachers’ responses to the use of a solar-powered science kit in elementary science learning - Devita Cahyani Nugraheny; Andi Suhandi; Cepi Riyana; Muslim Muslim (Universitas Kanjuruhan Malang, 2026)
Solar powered science kit is a learning media that is considered capable of helping students understand the concept of renewable energy through direct experience and simple experiments. This study aims to describe students' responses to the use of Solar Powered Science Kit as a learning media in elementary schools. The research method uses a qualitative descriptive approach. The results of the study show that students gave positive responses to the media, including increased learning motivation, ease of understanding energy concepts, student activeness in practical activities, and the emergence of critical attitudes towards environmental issues and alternative energy. Based on the results of the study, it can be concluded that students have a good response to the use of Powered Science Kit media in learning and assess this media according to the characteristics of students in elementary schools.